Effect of a multispecies probiotic on reducing the incidence of antibiotic-associated diarrhoea in children: a protocol for a randomised controlled trial - Hania Szajewska; Jan Łukasik (BMJ Open)
Introduction Certain individual probiotic strains have been proven to be effective in reducing the risk of antibiotic-associated diarrhoea (AAD). However, the effects of using multispecies probiotics (MPs) remain unclear. We aim to assess the effectiveness of a specific MP preparation (Winclove 612) in reducing the incidence of AAD in children.Methods and analysis A total of 350 children aged 6 months to 18 years, undergoing antibiotic treatment, will be randomly allocated to receive either a MP consisting of two strains of Bifidobacterium (B. bifidum W23 and B. lactis W51) and six strains of Lactobacillus (L. acidophilus W37, L. acidophilus W55, L. paracasei W20, L. plantarum W62, L. rhamnosus W71 and L. salivarius W24) at a total dose of 1010 colony-forming units daily, or a placebo, from the first day of antibiotic treatment until 7 days after antibiotic cessation, up to a maximum of 17 days. The primary outcome will be the incidence of AAD, defined as ≥3 loose or watery stools (a score of A on the Amsterdam Infant Stool Scale or a score of 5–7 on the Bristol Stool Form scale) in 24 hours, caused either by Clostridium difficile or of otherwise unexplained aetiology, occurring during the intervention period. The secondary outcomes will include the incidence of AAD according to alternative definitions; the incidence of any kind of diarrhoea; the duration of diarrhoea; the need for hospitalisation; intravenous rehydration or discontinuation of antibiotic treatment due to diarrhoea; adverse events; and the intestinal microbiota composition.Ethics and dissemination The study protocol is approved by the Ethics Committee of the Medical University of Warsaw. The findings will be published in a peer-reviewed journal and submitted to relevant conferences.Date and protocol version identifier 14/10/2017.Trial registration number NCT03334604; Pre-results.